Chemical Composition and Bioactive Properties of Purple French Bean (Phaseolus vulgaris L.) as Affected by Water Deficit Irrigation and Biostimulants Application - Fernandes, Ângela; Figueiredo, Sara; Finimundy, Tiane C.; Pinela, José; Tzortzakis, Nikos G.; Ivanov, Marija; Sokovic, Marina; Ferreira, Isabel C. F. R.; Petropoulos, Spyridon A.; Barros, Lillian (My University, 2021)
Biostimulants are a novel and eco-friendly agronomic tool with practical applications in alleviating negative effects of environmental stressors. The present work studied the effects of three biostimulant products (Nomoren (N), Twin-Antistress (TW), and X-Stress (XS)) under normal irrigation (W+) and water deficit irrigation conditions (W-) on the nutritional, chemical composition and bioactive properties of common bean fresh pods. A variable effect of biostimulants and water deficit irrigation was observed on nutritional value parameters, while fructose and sucrose were the main detected sugars, especially in NW+ and CW-treatments. Oxalic, malic, and citric acid were the main detected organic acids, while γ-and total tocopherol content was the highest in TWW+. (+)-Catechin and (-)-epicatechin were the most abundant phenolic compounds, especially in the NW-treatment. A variable antioxidant capacity was observed for the Thiobarbituric Acid Reactive Substances (TBARS) and Oxidative Haemolysis assays (OxHLIA), while TWW+ extracts showed the best overall results against the tested fungi. In conclusion, the tested biostimulants had a positive effect on chemical composition and bioactivities of purple bean depending on the irrigation regime.
Keywords: Antimicrobial properties; Antioxidant activity; Bioactive properties; Common bean; Fatty acids; Organic acids; Phenolic compounds; Proximate analyses; Tocopherols; Water deficit irrigation